Avaliação da ação de nanopartículas magnéticas na função cardiovascular de ratos - Nunes, Allancer Divino de Carvalho (2014)
Magnetic Nanoparticles (MNPs) have been used for various biomedical applications. Importantly, manganese ferrite-based nanoparticles have a useful magnetic resonance imaging characteristics and potential for magnetic hyperthermia treatment, but their effects in the cardiovascular system are poorly reported. Thus, the objectives of this study were to determine the cardiovascular effects of four different types of manganese ferrite-based nanoparticles: albumin-coated (MnFe2O4 Albumin); citrate-coated (MnFe2O4 Citrate); tripolyphosphate-coated (MnFe2O4 Phosphate); and bare nanoparticles (MnFe2O4 Ionic). The direct effects of the MNPs on cardiac contractility were evaluated in isolated perfused rat hearts. The MnFe2O4 Citrate, but not MnFe2O4 Phosphate and MnFe2O4 Ionic induced a transient decreased in the Left Ventricular End Systolic Pressure. The MnFe2O4 Phosphate and MnFe2O4 Ionic, but not MnFe2O4 Citrate induced an increase in Left Ventricular End Diastolic Pressure which resulted decrease in a Left Ventricular End Developed Pressure. Indeed, MnFe2O4 Phosphate and MnFe2O4 Ionic also caused a decrease in the maximum dP/dt and minimum dP/dt. The three MNPs studied induced an increase in the perfusion pressure of isolated hearts. It is important to note that the ionic nanoparticle induced more significant changes in cardiac function. Interestingly, coating the bare nanoparticles with albumin reverted the MnFe2O4 Ionic-induced cardiac effects. MnFe2O4 Ionic, but not MnFe2O4 Phosphate or MnFe2O4 Citratre, induced a slight vasorelaxant effect in the isolated aortic rings. None of the MNPs were able to change heart rate or arterial blood pressure in conscious rats. In summary, the responses on ventricular function were found to be strongly dependent upon the surface nanoparticles coating layer. Also, although the MNPs were able to induce effects ex vivo, no significant changes were observed in vivo. Thus, given the proper dosages, these MNPs should be considered for possible therapeutic applications.